Evaluation of managed aquifer recharge in the Central Highlands of Vietnam - Pavelic, Paul; Chu Thai Hoanh; D'Haeze, Dave; Bui Ngoc Vinh; Viossanges, Mathieu; Do Thanh Chung; Le Quang Dat; Ross, Andrew (Elsevier, 2022)
Study region: Dak Lak province in the Central Highlands of Vietnam Study focus: Intensification of agriculture has resulted in unsustainably high levels of groundwater use in the Central Highlands. High monsoonal rainfall provides opportunities to boost groundwater storage through managed aquifer recharge (MAR), yet experience with MAR in the region is absent. In response, five farm-scale pilots were implemented in collaboration with local farmers whereby runoff from roofs and fields was recharged into shallow dug wells. The pilots were closely monitored over three years. New hydrological insights for the region: MAR pilots exhibited large contrasts in performance, with volumes recharged ranging from 5 to 530 m3 per year. Pilot sites with cleaner roof runoff water performed best, whilst those using more turbid water from unpaved roads performed worst. Water quality analyses did not identify parameters of major concern for irrigation. Field data and modelling indicate that the size of the recharge water plumes are small relative to the high groundwater velocities making the recharge water difficult to recover from the recharge well in this setting. Water is however contained locally, providing potential for improved water availability within the local area. Farmer attitudes towards MAR vary in response to the technical performance and a range of socioeconomic factors. These findings may provide insights for researchers or practitioners from other regions where groundwater dependence is high but experience in MAR is lacking.